Muhammad Goziy and His Leiterary Heritage - Nazmiya Muslihiddinovna, Muhitdinova (International Journal of Psychosocial Rehabilitation, 2020)
The article is devoted to the definition of the place and the people who contributed to the development of creativity but whose lives have not been sufficiently studied. Mukhammad Gaziy was among those representatives popular with his works in the Kokand literary environment of Uzbek literature (the end of the 18th century and the first half of the 19th century). The verses of the poet are analyzed according to the manuscript of the collection made by him. The role and the value of the creativity of the poet in Uzbek literature, which are defined along with the great art skills and the importance of his creativity and which were significant in the further development of Uzbek literature as a whole, are especially emphasized.